Respuesta :

9514 1404 393

Answer:

  1. (f×g)(x) = 2x^2 +2x
  2. (f×g)(x) = 6y^2 -11y -35

Step-by-step explanation:

The distributive property applies.

1. (fg)(x) = f(x)·g(x) = (2x)·(x +1)

  (f×g)(x) = 2x^2 +2x

__

2. (fg)(x) = f(x)·g(x) = (2y -7)·(3y +5) = 2y(3y +5) -7(3y +5)

  (f×g)(x) = 6y^2 -11y -35

_____

Additional comment

Please note in problem 2 that the function argument is x and the variable in the given expressions is y. This means the function value is exactly and only 6y^2 -11y -35 for any value of x. It does not change when x changes. (We suspect a typo.)